Acrylate modified polyurethane hot melt adhesive as well as preparation method and application thereof
By using specific solid electrolytes and other compounds in polyurethane hot-melt adhesives, the problem of insufficient bonding strength of existing electrically detachable polyurethane hot-melt adhesives is solved, achieving the dual functions of high bonding strength and disassembly when electricity is applied. Suitable for high performance removable adhesive applications.
Patent Information
- Application Number
- CN202411460623.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
Although the existing electrically disassembleable polyurethane hot melt adhesive can be decomposed under power-on conditions, its bonding strength is far from that of traditional polyurethane hot melt adhesive, and it is difficult to meet the actual application needs.
By introducing oxide -based solid -state electrolytes and/or sulfide base solid electrolytes in polyurethane thermal melting glue, and combined with the use of sirriiner coupling agents and acrylic compounds to regulate the proportion of each component The function of disassembling.
The function of disassembling can be disassembled under power -powered conditions, while maintaining high adhesion strength, which significantly improves the reliability and performance of traditional electric disassembly adhesives.
Smart Images

Figure BDA0005091765610000141
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyurethane hot melt adhesives, and in particular relates to an acrylate modified polyurethane hot melt adhesive and a preparation method and application thereof. Background Art
[0002] Reactive polyurethane hot melt adhesives are often used to bond and fix electronic product components in electronic products such as smartphones, tablets, smart watches, and TWS headsets. Electronic product components bonded with reactive polyurethane hot melt adhesives are often of high value. When poor assembly, after-sales product repairs, or recycling of valuable electronic product components occur, it is usually necessary to disassemble some of the bonded components. Therefore, the adhesive is usually required to have excellent bonding reliability while being easy to disassemble under certain conditions.
[0003] Reactive polyurethane hot melt adhesive is mainly composed of isocyanate-terminated oligomers. The isocyanate groups in the isocyanate-terminated oligomers can react with moisture in the air and form a cross-linked chemical structure after complete curing, thereby achieving high bonding strength. However, the covalent bonds obtained by the reaction of isocyanate groups with moisture are irreversible, and the cross-linked structure is difficult to destroy. It is usually difficult to disassemble the adhesive after complete curing. If the bonded materials need to be separated, it is often necessary to use large external forces, high temperatures, chemical reagents and other conditions, and the bonded materials may be damaged during the disassembly of the adhesive, resulting in large economic losses.
[0004] In recent years, there are also technologies that add liquid electrolytes such as alkali metal salts and solvated matrices to polyurethane hot melt adhesives to give them the ability to be disassembled under power-on conditions. However, although the existing electrically disassembleable polyurethane hot melt adhesives have the function of being disassembled under power-on conditions, they still have a large gap in performance such as bonding strength compared to traditional widely used polyurethane hot melt adhesives. The electrically disassembleable polyurethane hot melt adhesives developed by existing technologies are still difficult to meet the needs of actual application scenarios.
[0005] Therefore, there is an urgent need to develop an adhesive that can be disassembled under power-on conditions and has excellent bonding properties to meet the market demand for high-performance detachable adhesives. Summary of the invention
[0006] The first purpose of the present invention is to provide an acrylate-modified polyurethane hot melt adhesive with high bonding strength and electrical disassembly, as well as a preparation method and application thereof, in view of the disadvantage that the electrically disassemblyable polyurethane hot melt adhesive in the prior art has poor bonding strength.
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned acrylate-modified polyurethane hot melt adhesive.
[0008] The third object of the present invention is to provide the application of the above-mentioned acrylate modified polyurethane hot melt adhesive in the bonding of electronic products.
[0009] Specifically, the raw materials for preparing the acrylate-modified polyurethane hot melt adhesive provided by the present invention contain a polyol compound, a polyisocyanate compound, a solid electrolyte, a silane coupling agent, an acrylate compound and a photoinitiator, as well as an optional catalyst and a water absorbent; the solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte; the mass ratio of the solid electrolyte, the silane coupling agent, the acrylate compound and the polyol compound is (10-45):(10-30):(15-85):100.
[0010] In existing polyurethane hot melt adhesives, detachable properties are usually achieved by adding liquid electrolytes. However, although the use of liquid electrolytes can give polyurethane hot melt adhesives the ability to be detached when powered on, it will seriously affect the bonding strength of the polyurethane hot melt adhesive. In this regard, after in-depth research, the inventors of the present invention found that one of the main reasons for the significant decrease in the bonding strength of polyurethane hot melt adhesives is that the liquid electrolyte is a liquid substance and is difficult to solidify. After the polyurethane hot melt adhesive is completely solidified, the unsolidified liquid electrolyte will remain in the curing system to form a "plasticizer", which changes the internal structure of the curing system. The presence of this "plasticizer" has a large negative impact on the bonding strength and will greatly reduce the bonding performance of the polyurethane hot melt adhesive; in addition, due to the poor compatibility between inorganic solid electrolyte materials and organic polyurethane hot melt adhesives, it is usually difficult to evenly disperse them in the polyurethane hot melt adhesive system, which limits its application in electrically disassembled polyurethane hot melt adhesives.
[0011] The key to the present invention is to disregard the limitation of the traditional concept that inorganic solid electrolytes are difficult to be evenly dispersed in the polyurethane hot melt adhesive system and should be used with caution. A specific solid electrolyte (oxide-based solid electrolyte and / or sulfide-based solid electrolyte) is introduced into the polyurethane hot melt adhesive system in the presence of a silane coupling agent and an acrylate compound, and the ratio between the solid electrolyte, the silane coupling agent, the acrylate compound and the polyol compound is regulated, so that the polyurethane hot melt adhesive obtained not only has detachable properties, but also has good bonding strength. It is speculated that the reason may be that: the oxide-based solid electrolyte and the sulfide-based solid electrolyte themselves have high ionic conductivity in the solid state, and can undergo Faraday electrochemical reactions under power-on conditions, weakening the bonding force at the adhesive bonding interface, thereby giving the polyurethane hot melt adhesive detachable properties; the acrylate compound can well disperse the oxide-based solid electrolyte and the sulfide-based solid electrolyte, thereby facilitating the uniform dispersion of the oxide-based solid electrolyte and the sulfide-based solid electrolyte in the polyurethane adhesive, and at the same time, the bridging effect of the silane coupling agent can further assist the oxide-based solid electrolyte and the sulfide-based solid electrolyte in the polyurethane adhesive. The dispersion in the agent, that is, the synergistic combination of acrylate compounds and silane coupling agents can well ensure that the two specific solid electrolytes, oxide-based solid electrolytes and sulfide-based solid electrolytes, have good compatibility with polyurethane hot melt adhesives and can be well dispersed in the polyurethane hot melt adhesive system. At the same time, the oxide-based solid electrolytes and sulfide-based solid electrolytes will not form "plasticizers" after the polyurethane hot melt adhesive is cured, causing its internal structure to change to affect the bonding strength. On the contrary, the oxide-based solid electrolytes and sulfide-based solid electrolytes themselves can also be used as fillers to reinforce the colloid, thereby improving the bonding performance of the polyurethane hot melt adhesive. In addition, acrylate compounds can undergo a curing reaction in the presence of a photoinitiator, which not only solves the problem that the existing solvated matrix is difficult to cure, but also has a faster curing speed than traditional polyurethane adhesives. At the same time, by regulating the proportion of acrylate compounds in the adhesive system, an adhesive that can be applied to opaque conductive substrates can be effectively prepared. DETAILED DESCRIPTION
[0012] The raw materials for preparing the polyurethane hot melt adhesive provided by the present invention contain a polyol compound, a polyisocyanate compound, a solid electrolyte, a silane coupling agent, an acrylate compound and a photoinitiator, as well as an optional catalyst and a water absorbent. The mass ratio of the solid electrolyte to the polyol compound is (10-45):100, such as 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100 or any value therebetween. The mass ratio of the silane coupling agent to the polyol compound is (10-30):100, such as 10:100, 15:100, 20:100, 25:100, 30:100 or any value therebetween. The mass ratio of the acrylic acid ester compound to the polyol compound is (15-85):100, such as 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100, 55:100, 60:100, 65:100, 70:100, 75:100, 80:100, 85:100 or any value therebetween. The solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte. Among them, the structural features of the oxide-based solid electrolyte are preferably selected from at least one of NASICON type, garnet type and perovskite type. The structural features of the sulfide-based solid electrolyte are preferably selected from at least one of amorphous, crystalline and glass-ceramic types.
[0013] In the present invention, the content of the polyol compound is preferably 30 to 65 parts by weight, such as 30, 32, 35, 38, 40, 42, 45, 48, 50, 52, 55, 58, 60, 62, 65 parts by weight or any value therebetween; the content of the polyisocyanate compound is preferably 5 to 20 parts by weight, such as 5, 8, 10, 12, 15, 18, 20 parts by weight or any value therebetween; the content of the solid electrolyte is preferably 5 to 15 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween; the content of the silane coupling agent is preferably 5 to 10 parts by weight, such as 5, 6, 7, 8, 9, 10 parts by weight or any value therebetween; the content of the acrylic acid is preferably 5 to 20 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween The content of the acrylate compound is preferably 10 to 30 parts by weight, such as 10, 12, 15, 18, 20, 22, 25, 28, 30 parts by weight or any value therebetween; the content of the photoinitiator is preferably 0.5 to 5 parts by weight, such as 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight or any value therebetween; the content of the catalyst is preferably 0 to 2 parts by weight, such as 0, 0.1, 0.2, 0.5, 0.8, 1, 1.5, 2 parts by weight or any value therebetween; the content of the water absorbent is preferably 0 to 2 parts by weight, such as 0, 0.1, 0.2, 0.5, 0.8, 1, 1.5, 2 parts by weight or any value therebetween.
[0014] In the present invention, the solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte. The ionic conductivity of the oxide-based solid electrolyte and / or the sulfide-based solid electrolyte at room temperature is generally 10 -4 S / cm or more, and its source and type can be various existing options. The D50 or D90 particle size of the solid electrolyte is preferably 0.3 to 30 μm, such as 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm or any value therebetween. When the D50 or D90 particle size of the solid electrolyte is within the above preferred range, it is more conducive to the uniform dispersion of the solid electrolyte in the polyurethane hot melt adhesive system, giving it good electrical disassembly performance, and it is also more conducive to the reinforcing role of the solid electrolyte as a filler, and cooperating with other raw material components to improve the bonding performance of the polyurethane hot melt adhesive system. The term "D50 or D90 particle size" refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50% or 90%.
[0015] In the present invention, the number average molecular weight (Mn) of the polyol compound is preferably 1000-4000 g / mol, such as 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol, 3500 g / mol, 4000 g / mol or any value therebetween. The type and source of the polyol compound can be various existing choices, preferably at least one of polyester polyol, polyether polyol, polycarbonate polyol and polyalkylene polyol. Specifically, the polyester polyol can be a polyester polyol obtained by the reaction of a polycarboxylic acid and a polyol, or a poly-ε-caprolactone polyol obtained by ring-opening polymerization of ε-caprolactone. Wherein, the polycarboxylic acid is preferably at least one of terephthalic acid, isophthalic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decamethylene dicarboxylic acid and dodecamethylene dicarboxylic acid. The polyol is preferably at least one of ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol and cyclohexanediol. The polyether polyol may be at least one of a random copolymer, a block copolymer and a bisphenol-type polyoxyalkylene modified body of ethylene glycol, propylene glycol, tetrahydrofuran, 3-methyltetrahydrofuran or a derivative thereof. Wherein, the bisphenol-type polyoxyalkylene modified body is a polyether polyol obtained by adding alkylene oxide to the active hydrogen portion of the bisphenol-type molecular skeleton, and may be a random copolymer and / or a block copolymer. The alkylene oxide is preferably at least one of ethylene oxide, propylene oxide, butylene oxide and isobutylene oxide. The polycarbonate polyol may be exemplarily polycarbonate 1,6-hexanediol ester diol, polycarbonate-1,4-butanediol-1,6-hexanediol ester diol, polycarbonate-1,5-pentanediol-1,6-hexanediol ester diol, polycarbonate caprolactone hexanediol, polycarbonate-1,4-cyclohexanedimethanol-1,6-hexanediol ester diol, polyethylene carbonate diol, polypropylene carbonate diol, polybutylene carbonate diol and polyhexane carbonate diol. The polyalkylene polyol may be exemplarily polybutadiene polyol, hydrogenated polybutadiene polyol and hydrogenated polyisoprene polyol.
[0016] In the present invention, the type and source of the polyisocyanate compound can be various existing options, preferably at least one selected from isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, meta-xylylene diisocyanate, tetramethylxylylene diisocyanate, norbornane dimethylene isocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.
[0017] In the present invention, the type and source of the silane coupling agent can be various existing options, preferably at least one of mercaptosilane, epoxysilane, aminosilane, alkenylsilane and isocyanate silane, and specific examples thereof include but are not limited to: 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxy At least one of propoxypropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(methyl)acryloxypropyltrimethoxysilane, 3-(methyl)acryloxypropyltriethoxysilane, 3-(methyl)acryloxypropylmethyldimethoxysilane, 3-(methyl)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane. The addition of the silane coupling agent helps to promote the uniform dispersion of the solid electrolyte in the polyurethane hot melt adhesive system, thereby giving the polyurethane hot melt adhesive system the property of being electrically disassembled and having good bonding properties.
[0018] In the present invention, the acrylate compound can be various existing photocurable acrylate monomers, such as octadecyl acrylate, tetramethylene glycol acrylate, dodecyl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, tridecyl acrylate, trimethylolpropane formal acrylate, monoacrylate of methoxy polyethylene glycol, alkoxylated tetramethylene glycol acrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, tetraethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate and 1,3-butanediol dimethacrylate.
[0019] In the present invention, the photoinitiator can be any of the existing various compounds that absorb energy in the ultraviolet light region or the visible light region to generate free radicals to initiate the polymerization reaction of acrylic functional groups, such as at least one of benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds and thioxanthone.
[0020] In the present invention, the type and source of the catalyst can be various existing options, preferably at least one selected from dibutyltin dilaurate, stannous octoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.
[0021] In the present invention, the type and source of the water absorbent can be various existing options, preferably at least one selected from molecular sieve desiccant, oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.
[0022] The preparation method of the acrylate-modified polyurethane hot melt adhesive provided by the present invention comprises uniformly mixing a polyol compound, a polyisocyanate compound, a solid electrolyte, a silane coupling agent, an acrylate compound, a photoinitiator, and an optional catalyst and a water absorbent to obtain an acrylate-modified polyurethane hot melt adhesive. The present invention does not particularly limit the mixing method. In a preferred embodiment, the mixing step comprises: S1, dehydrating the polyol compound, the solid electrolyte, the silane coupling agent, the acrylate compound, and the optional water absorbent to obtain a pretreated product; S2, stirring the pretreated product and the polyisocyanate compound and the optional catalyst at 70 to 90° C. for 1 to 5 hours to obtain a prepolymer; S3, uniformly mixing the prepolymer and the photoinitiator to obtain an acrylate-modified polyurethane hot melt adhesive.
[0023] In the preparation process of the above-mentioned acrylate modified polyurethane hot melt adhesive, in step S1, the conditions for vacuum dehydration include: the temperature is preferably 100-120°C, such as 100°C, 105°C, 110°C, 115°C, 120°C or any value therebetween; the time is preferably 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween; the stirring speed is preferably 100-200r / min, such as 100r / min, 120r / min, 150r / min, 180r / min, 200r / min or any value therebetween.
[0024] In the preparation process of the above-mentioned acrylate modified polyurethane hot melt adhesive, in step S2, the stirring reaction conditions include: the temperature is preferably 70-90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; the time is preferably 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween; the stirring speed is preferably 100-200r / min, such as 100r / min, 120r / min, 150r / min, 180r / min, 200r / min or any value therebetween.
[0025] In the preparation process of the above-mentioned acrylate modified polyurethane hot melt adhesive, in step S3, the mixing conditions include: the temperature is preferably 70-90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; the time is preferably 30min-2h, such as 30min, 40min, 50min, 1h, 1.5h, 2h or any value therebetween; the stirring speed is preferably 100-200r / min, such as 100r / min, 120r / min, 150r / min, 180r / min, 200r / min or any value therebetween.
[0026] The acrylate modified polyurethane hot melt adhesive provided by the present invention can be applied to an adhesive substrate that can be electrified, and the voltage for electrification disassembly can be 1 to 100V, such as 1V, 5V, 9V, 10V, 20V, 50V, 60V, 80V, 100V or any value therebetween, and the time for electrification disassembly can be 1s to 60min, such as 1s, 2s, 5s, 10s, 30s, 50s, 1min, 2min, 5min, 10min, 20min, 30min, 40min, 50min, 60min or any value therebetween. In addition, the adhesive substrate used by the reactive polyurethane hot melt adhesive is preferably a conductive substrate.
[0027] The present invention will be described in detail below through specific embodiments.
[0028] The parts involved in the following examples and comparative examples are all parts by weight.
[0029] The raw materials and sources in the following examples and comparative examples are as follows:
[0030] Polyester polyol DYNACOLL 7380, purchased from Evonik Specialty Chemicals, Mn = 3500 g / mol; polyoxypropylene ether diol, purchased from Dow Chemical Company, brand name Voranol-2120, Mn = 2000 g / mol; polyhexanediol adipate diol, purchased from Qingdao Xinyutian Chemical Co., Ltd., brand name POL-538, Mn = 3000 g / mol; poly(ethylene phthalate) diol, purchased from Stepan, brand name PS-70L, Mn = 1600 g / mol; poly(hexanediol) adipate diol, purchased from Qingdao Xinyutian Chemical Co., Ltd., brand name POL-538, Mn = 3000 g / mol; poly(ethylene phthalate) diol, purchased from Stepan, brand name PS-70L, Mn = 1600 g / mol; Diacid neopentyl glycol ester diol, purchased from Qingdao Xinyutian Chemical Co., Ltd., brand POL-756, Mn=2000g / mol; polyoxypropylene ether diol, purchased from Dow Chemical Company, brand Voranol-220-110, Mn=1000g / mol; polybutylene adipate diol, purchased from Qingdao Xinyutian Chemical Co., Ltd., brand POL-356, Mn=2000g / mol; polytetrahydrofuran ether diol, purchased from BASF (BASF), brand PolyTHF 1000, Mn=1000g / mol; polycaprolactone diol, purchased from Daicel Corporation, brand PLACCEL 240, Mn=4000g / mol.
[0031] NASICON oxide-based solid electrolyte LATP, D50 = 0.3 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LATP-300, ionic conductivity ≥ 6*10 at room temperature -4 S / cm; sulfide-based solid electrolyte FL-LPSC, D50 = 30 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LPSC-30000, ionic conductivity at room temperature is 1*10 -2 S / cm; garnet-type oxide-based solid electrolyte FL-GTEP, D50 = 0.5 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand GTEP-500, ionic conductivity ≥ 8*10 at room temperature -4 S / cm; sulfide-based solid electrolyte FL-LPSC, D90 = 20 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LPSC-20000, ionic conductivity at room temperature is 6*10 -3 S / cm; NASICON oxide-based solid electrolyte LATP, D50 = 0.1 μm, purchased from Bluegoo New Energy Technology Co., Ltd., brand LG1117, ionic conductivity at room temperature is 5*10 -4 S / cm~1*10 -3S / cm; sulfide-based solid electrolyte LGPS, D50 = 50 μm, purchased from Shenzhen ASML New Energy Co., Ltd., brand LGPS-50 μm, ionic conductivity at room temperature is ≥7*10 -3 S / cm; Polyethylene oxide PEO solid electrolyte, purchased from Cluder, brand E-30, ionic conductivity at room temperature is 6.29*10 -6 S / cm.
[0032] The p-toluenesulfonyl isocyanate water absorbent was purchased from Borchers, Germany, with the brand name Additive TI; the triethyl orthoformate water absorbent was purchased from Borchers, Germany, with the brand name Additive OF; the adsorbent molecular sieve water absorbent was purchased from ARkEMA, with the brand name Siliporite SA1702.
[0033] Example 1
[0034] By weight, 23.61 parts of polyester diol Dynacoll 7380 with a number average molecular weight of 3500, 26.98 parts of polyoxypropylene ether diol Voranol-2120 with a number average molecular weight of 2000, 10.0 parts of tetrahydrofuran acrylate, 10.0 parts of triethylene glycol diacrylate, 8.00 parts of NASICON type oxide-based solid electrolyte LATP (D50 = 0.6 μm), 7.5 parts of 3-glycidoxypropyltrimethoxysilane, and 1.5 parts of water absorbent Additive TI, heated to 110 ° C, vacuum dehydrated at 150 r / min stirring condition for 2 h, then cooled to 80 ° C, added 10.12 parts of diphenylmethane-4,4'-diisocyanate (MDI) and 0.3 parts of dibutyltin dilaurate, reacted at 150 r / min stirring condition for 2 h, then added 2.0 parts of photoinitiator TPO, mixed at 150 r / min stirring condition for 1 h and then discharged to obtain acrylate modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0035] Example 2
[0036] By weight, 17.63 parts of poly(hexanediol adipate) diol POL-538 with a number average molecular weight of 3000, 28.21 parts of poly(diethylene phthalate) diol PS-70L with a number average molecular weight of 1600, 15.0 parts of isooctyl acrylate, 10.0 parts of diethylene glycol diacrylate, 6.00 parts of sulfide-based solid electrolyte FL-LPSC (D90 = 20 μm), 5.5 parts of 3-mercaptopropyltrimethoxysilane, and 0.5 parts of water absorbent Additive OF, heated to 110°C, vacuum dehydrated for 2 hours under stirring conditions at 150 r / min, then cooled to 80°C, 13.55 parts of dicyclohexylmethane-4,4'-diisocyanate (HMDI) and 0.6 parts of stannous octoate were added, reacted for 2 hours under stirring conditions at 150 r / min, and then 3.0 parts of photoinitiator 819 were added, mixed for 1 hour under stirring conditions at 150 r / min, and then discharged to obtain acrylate modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0037] Example 3
[0038] By weight, 14.13 parts of poly (neopentyl adipate glycol) diol POL-756 with a number average molecular weight of 2000, 28.25 parts of polyoxypropylene ether diol Voranol-220-110 with a number average molecular weight of 1000, 10.0 parts of tridecyl acrylate, 5.0 parts of tetraethylene glycol diacrylate, 11.00 parts of sulfide-based solid electrolyte FL-LPSC (D50 = 30 μm), 8.8 parts of 3-aminopropyl trimethoxysilane, and 1.2 parts of water absorbent Siliporite SA1702 was heated to 110°C, vacuum dehydrated for 2 h at 150 r / min stirring, then cooled to 80°C, 19.42 parts of diphenylmethane-4,4'-diisocyanate (MDI) and 1.2 parts of 2,2-dimorpholinyl diethyl ether were added, and reacted for 2 h at 150 r / min stirring, and then 1.0 part of photoinitiator ITX was added, and the mixture was mixed for 1 h at 150 r / min stirring, and then discharged to obtain acrylate-modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0039] Example 4
[0040] By weight, 29.22 parts of polybutylene adipate diol POL-356 with a number average molecular weight of 2000, 4.87 parts of polytetrahydrofuran ether diol PolyTHF 1000 with a number average molecular weight of 1000, 14.0 parts of isodecyl acrylate, 14.0 parts of 1,4-butanediol diacrylate, 14.00 parts of garnet-type oxide-based solid electrolyte FL-GTEP (D50 = 0.5 μm), 9.5 parts of vinyl trimethoxysilane, and 1.5 parts of water absorbent Additive TI, heated to 110 ° C, vacuum dehydrated at 150 r / min stirring condition for 2 h, then cooled to 80 ° C, added 8.22 parts of isophorone diisocyanate (IPDI) and 0.7 parts of bismuth isooctanoate, reacted at 150 r / min stirring condition for 2 h, then added 4.0 parts of photoinitiator 369, mixed at 150 r / min stirring condition for 1 h and then discharged to obtain acrylate modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0041] Example 5
[0042] By weight, 46.57 parts of polycaprolactone diol PLACCEL 240 with a number average molecular weight of 4000, 17.46 parts of polytetramethylene glycol PTMEG 3000 with a number average molecular weight of 3000, 6.0 parts of trimethylolpropane formal acrylate, 7.0 parts of tripropylene glycol diacrylate, 9.00 parts of NASICON type oxide-based solid electrolyte LATP (D50 = 0.3 μm), 7.0 parts of 3-isocyanate propyl trimethoxysilane, and 0.3 parts of water absorbent Additive OF, heated to 110°C, vacuum dehydrated for 2 hours under stirring conditions at 150 r / min, then cooled to 80°C, 5.87 parts of hexamethylene diisocyanate (HDI) and 0.2 parts of zinc isooctanoate were added, reacted for 2 hours under stirring conditions at 150 r / min, and then 0.6 parts of photoinitiator 184 were added, mixed for 1 hour under stirring conditions at 150 r / min, and then discharged to obtain acrylate modified polyurethane hot melt adhesive, which was vacuum sealed and stored away from light.
[0043] Example 6
[0044] An acrylate-modified polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same weight portion of NASICON-type oxide-based solid electrolyte LATP with D50=0.1 μm was used instead of NASICON-type oxide-based solid electrolyte LATP with D50=0.6 μm, and the other conditions were the same as those in Example 1 to obtain an acrylate-modified polyurethane hot melt adhesive, which was vacuum-sealed and stored away from light.
[0045] Example 7
[0046] An acrylate-modified polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same weight portion of sulfide-based solid electrolyte LGPS-50μm with D50=50μm was used instead of NASICON-type oxide-based solid electrolyte LATP with D50=0.6μm, and the other conditions were the same as in Example 1 to obtain an acrylate-modified polyurethane hot melt adhesive, which was vacuum-sealed and stored away from light.
[0047] Comparative Example 1
[0048] By weight, 38.35 parts of poly(neopentyl adipate glycol) diol POL-756 with a number average molecular weight of 2000, 19.17 parts of poly(butylene adipate glycol) diol POL-356 with a number average molecular weight of 2000, 0.5 parts of 3-mercaptopropyltrimethoxysilane, 20.0 parts of propylene carbonate, 6.00 parts of lithium trifluoromethanesulfonate, and 1.2 parts of water absorbent Additive TI were heated to 110°C, vacuum dehydrated for 2 hours under stirring conditions of 150 r / min, and then cooled to 80°C, 14.38 parts of diphenylmethane-4,4'-diisocyanate (MDI) and 0.4 parts of stannous octoate were added, reacted for 2 hours under stirring conditions of 150 r / min, and then 1.0 parts of photoinitiator 184 were added, mixed for 1 hour under stirring conditions of 150 r / min, and then discharged to obtain a reference acrylate-modified polyurethane hot melt adhesive, which was vacuum-sealed and stored away from light.
[0049] Comparative Example 2
[0050] A reference acrylate-modified polyurethane hot melt adhesive was prepared according to the method of Example 1, except that NASICON-type oxide-based solid electrolyte LATP (D50=0.6 μm) was not added. The other conditions were the same as those in Example 1 to obtain a reference acrylate-modified polyurethane hot melt adhesive, which was vacuum-sealed and stored away from light.
[0051] Comparative Example 3
[0052] A reference acrylate-modified polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same weight portion of polyethylene oxide PEO solid electrolyte (Croode Company, brand E-30, ionic conductivity of 6.29*10-6S / cm at room temperature) was used instead of NASICON-type oxide-based solid electrolyte LATP (D50=0.6μm), and the other conditions were the same as in Example 1 to obtain a reference acrylate-modified polyurethane hot melt adhesive, which was vacuum-sealed and stored away from light.
[0053] Comparative Example 4
[0054] A reference acrylate-modified polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the amount of 3-glycidoxypropyltrimethoxysilane added was reduced to 1.0 part. The other conditions were the same as those of Example 1 to obtain a reference acrylate-modified polyurethane hot melt adhesive, which was vacuum-sealed and stored away from light.
[0055] Comparative Example 5
[0056] A reference polyurethane hot melt adhesive was prepared according to the method of Example 1, except that tetrahydrofuran acrylate and triethylene glycol diacrylate were not added, and the other conditions were the same as those of Example 1, thereby obtaining a reference polyurethane hot melt adhesive.
[0057] Comparative Example 6
[0058] A reference acrylate-modified polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the addition amounts of tetrahydrofuran acrylate and triethylene glycol diacrylate were increased to 50 parts, and the other conditions were the same as those of Example 1, to obtain a reference acrylate-modified polyurethane hot melt adhesive.
[0059] Test Case
[0060] The polyurethane hot melt adhesives prepared in the above examples and comparative examples were tested for bonding performance, heat resistance and high temperature and high humidity resistance before and after power on according to the following method. The results are shown in Table 1.
[0061] (1) Bond strength test at different curing times before power on: The acrylate-modified polyurethane hot melt adhesive obtained in the embodiment and the comparative example was dispensed at 110°C using a dispensing machine, and a rectangular adhesive line of 25 mm*4 mm was applied on a stainless steel substrate. Then, a 365 nm UV-LED light source was used to irradiate the adhesive with 2000 mJ / cm 2 Energy, after the irradiation, another stainless steel substrate was bonded on the stainless steel substrate. After the bonding was completed, the sample was cured in an environment of 25℃ and 50%RH for 1min, 15min and 1d. Then, the prepared bonding sample was run along the shear direction at a speed of 10mm / min using a universal material testing machine until the bonding of the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after curing for 1min, 15min and 1d was calculated based on the bonding area.
[0062] (2) Adhesive strength after power-on: The acrylate-modified polyurethane hot melt adhesive obtained in the examples and comparative examples was dispensed at 110°C using a dispensing machine to apply a 25 mm*4 mm rectangular adhesive line on a stainless steel substrate. The adhesive was then irradiated with 2000 mJ / cm2 of UV-LED light at 365 nm. 2energy. After the irradiation, another stainless steel substrate is bonded on the stainless steel substrate. After the bonding is completed, the sample is cured in an environment of 25°C and 50% RH for 24 hours to obtain a sample to be tested. The positive and negative wires of the DC power supply are clamped at both ends of the sample, and power is applied at 48V for 30 minutes or at 60V for 20 minutes. After the power-on is completed, the sample is removed, and a universal material testing machine is used to run the prepared bonding sample along the shear direction at a speed of 10mm / min until the sample fails to bond. The maximum force value displayed by the instrument is recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after power-on is calculated in combination with the bonding area (when the bonding strength is below 2MPa, it is removable).
[0063] (3) Heat resistance (80°C): The acrylate-modified polyurethane hot melt adhesive obtained in the examples and comparative examples was dispensed at 110°C using a dispensing machine, and a rectangular adhesive line of 25 mm*4 mm was applied on a stainless steel substrate. The adhesive was then irradiated with 2000 mJ / cm2 of UV-LED light at 365 nm. 2 Energy, after the irradiation, another stainless steel substrate is bonded on the stainless steel substrate. After the bonding, the sample is cured in an environment of 25℃ and 50%RH for 24h, and the bonded sample is placed in an oven at 80℃ for 20min. The prepared bonding sample is run at a speed of 10mm / min along the shear direction at 80℃ using a universal material testing machine until the sample fails to bond, and the maximum force value displayed by the instrument is recorded. The shear bonding strength of the adhesive to the stainless steel substrate in a high temperature environment of 80℃ is calculated based on the bonding area.
[0064] (4) High temperature and high humidity resistance (85°C, 85% RH): The acrylate-modified polyurethane hot melt adhesive obtained in the examples and comparative examples was dispensed at 110°C using a dispensing machine, and a rectangular adhesive line of 25 mm*4 mm was applied on a stainless steel substrate. The adhesive was then irradiated with 2000 mJ / cm2 of a 365 nm UV-LED light source. 2 Energy, after the irradiation, another stainless steel substrate is bonded on the stainless steel substrate. After the bonding is completed, the sample is cured in an environment of 25℃ and 50%RH for 24h, and the bonded sample is placed in a high temperature and high humidity oven at 85℃ and 85%RH for 7d. The prepared bonding sample is run along the shear direction at a speed of 10mm / min using a universal material testing machine until the sample fails to bond, and the maximum force value displayed by the instrument is recorded. The shear bonding strength of the adhesive to the stainless steel substrate after high temperature and high humidity aging is calculated based on the bonding area.
[0065] Table 1
[0066]
[0067] From the comparison of Examples 1 to 7 and Comparative Examples 1 to 6, it can be seen that the bonding strength of the acrylate-modified polyurethane hot melt adhesive provided by the present invention is significantly reduced after power is applied, and the function of easy disassembly can be achieved after the adhesive strength is reduced. At the same time, compared with the traditional electrical disassembly polyurethane hot melt adhesive with liquid electrolyte added, the present invention has better bonding strength, curing speed, and better heat resistance and high temperature and high humidity stability. While realizing the function of power-on disassembly, it significantly improves the defects of low bonding strength and poor reliability of traditional electrical disassembly adhesives. Therefore, by using a specific ratio of oxide-based solid electrolytes and / or sulfide-based solid electrolytes in combination with silane coupling agents and acrylate compounds, an acrylate-modified polyurethane hot melt adhesive with excellent bonding performance and power-on disassembly function can be effectively prepared, which has broad practical application prospects.
[0068] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. An acrylate modified polyurethane hot melt adhesive, characterized in that: The raw materials for preparing the acrylate-modified polyurethane hot melt adhesive contain a polyol compound, a polyisocyanate compound, a solid electrolyte, a silane coupling agent, an acrylate compound and a photoinitiator as well as an optional catalyst and a water absorbent; the solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte; the mass ratio of the solid electrolyte, the silane coupling agent, the acrylate compound and the polyol compound is (10-45):(10-30):(15-85):
100.
2. The acrylate modified polyurethane hot melt adhesive according to claim 1, characterized in that: The content of the polyol compound is 30 to 65 parts by weight, the content of the polyisocyanate compound is 5 to 20 parts by weight, the content of the solid electrolyte is 5 to 15 parts by weight, the content of the silane coupling agent is 5 to 10 parts by weight, the content of the acrylate compound is 10 to 30 parts by weight, the content of the photoinitiator is 0.5 to 5 parts by weight, the content of the catalyst is 0 to 2 parts by weight, and the content of the water absorbent is 0 to 2 parts by weight; Optionally, the ionic conductivity of the solid electrolyte at room temperature is 10 -4 S / cm or more; Optionally, the D50 or D90 particle size of the solid electrolyte is 0.3 to 30 μm.
3. The acrylate modified polyurethane hot melt adhesive according to claim 1, characterized in that: The number average molecular weight of the polyol compound is 1000 to 4000 g / mol; Optionally, the polyol compound is selected from at least one of polyester polyol, polyether polyol, polycarbonate polyol and polyalkylene polyol.
4. The acrylate modified polyurethane hot melt adhesive according to claim 1, characterized in that: The polyisocyanate compound is selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, meta-xylylene diisocyanate, tetramethylxylylene diisocyanate, norbornane dimethylene isocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.
5. The acrylate modified polyurethane hot melt adhesive according to claim 1, characterized in that: The silane coupling agent is selected from 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl methyl diethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3- At least one of oxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane.
6. The acrylate-modified polyurethane hot melt adhesive according to claim 1, characterized in that: The acrylate compound is selected from at least one of octadecyl acrylate, tetramethylene glycol acrylate, dodecyl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, tridecyl acrylate, trimethylolpropane formal acrylate, monoacrylate of methoxy polyethylene glycol, alkoxylated tetramethylene glycol acrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, tetraethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate and 1,3-butanediol dimethacrylate.
7. The acrylate-modified polyurethane hot melt adhesive according to claim 1, characterized in that: The photoinitiator is selected from at least one of benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds and thioxanthone.
8. The acrylate-modified polyurethane hot melt adhesive according to claim 1, characterized in that: The catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.
9. The acrylate-modified polyurethane hot melt adhesive according to claim 1, characterized in that: The water absorbent is selected from at least one of a molecular sieve desiccant, an oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.
10. The method for preparing the acrylate modified polyurethane hot melt adhesive according to any one of claims 1 to 9, characterized in that: The method comprises uniformly mixing a polyol compound, a polyisocyanate compound, a solid electrolyte, a silane coupling agent, an acrylate compound, a photoinitiator, and an optional catalyst and a water absorbent to obtain an acrylate-modified polyurethane hot melt adhesive.
11. The method for preparing the acrylate modified polyurethane hot melt adhesive according to claim 10, characterized in that: The mixing step comprises: S1, dehydrating the polyol compound, the solid electrolyte, the silane coupling agent, the acrylate compound and the optional water absorbent to obtain a pretreated product; S2, stirring the pretreated product, the polyisocyanate compound and the optional catalyst at 70-90° C. for 1-5 hours to obtain a prepolymer; S3. Evenly mix the prepolymer and the photoinitiator to obtain the acrylate-modified polyurethane hot melt adhesive.
12. Use of the acrylate modified polyurethane hot melt adhesive according to any one of claims 1 to 9 in bonding electronic products.